KEPEMIMPINAN PENDIDIKAN YANG INOVATIF - Syam, Aminuddin (AT-TA'LIM, 2012)
The government policy on autonomy of education should be followed by the inovation in many components of education institutions, especially in their management level. The appropriate management in autonomous era is that the existence of inovative leadership. In other words, they have clear vision, mission, will, and commitment to do inovations. Thus, the education institution under this inovative leadership will reach their aims based the autonomy demands quickly.